Non-invasive bio-electromagnetic monitoring of cerebrovascular function: a novel conductivity reactivity index (CRx) for optimal cerebral perfusion pressure in acute brain injury models - Xu, Jia; Li, Haochen; Wang, Feng; Yan, Lian; Jin, Gui; Chen, Mingsheng; Li, Gen; Qin, Mingxin (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe pressure reactivity index (PRx) is a key predictor of cerebrovascular function, widely used to guide and optimize therapeutic strategies in patients with acute brain injury. This study investigates a non-invasive bio-electromagnetic technique for monitoring and maintaining cerebrovascular function in a rabbit model of acute brain injury.MethodsA coaxial parallel double-coil sensor was designed to detect changes in intracranial electromagnetic properties, measured as magnetic induction phase shifts (MIPS), which reflect cerebral blood volume fluctuations. A cerebrovascular function monitoring platform was constructed with this sensor, a vector network analyzer, a LabVIEW software platform, and a physiological signal acquisition device to record the MIPS and arterial blood pressure (ABP). In the animal experiment, a novel cerebrovascular function index Conductivity Reactivity index (CRx), established with MIPS and ABP, was to assess optimal cerebral blood perfusion pressure (CPP) for maintaining the cerebrovascular function in four gradients of CPP in acute brain injury model.ResultsThe results found that the CRx (−0.072 ± 0.203) was a significant negative correlation with the PRx (0.223 ± 0.203) (r = −0.447, P = 0.003). Under the optimal CPP determined by the CPP-CRx curve, the mean CRx (0.104 ± 0.170) indicated normal cerebrovascular function, which was significantly different from the other states (CRx = −0.127 ± 0.061, p = 0.009).DiscussionThe study demonstrated that CRx has potential to reflect cerebrovascular function dynamics and assess optimal CPP, demonstrating the potential of bio-electromagnetic technology as a noninvasive indicator for monitoring cerebrovascular function.